2021
DOI: 10.1186/s40479-021-00166-6
|View full text |Cite
|
Sign up to set email alerts
|

Examining emotion regulation in binge-eating disorder

Abstract: Background Inefficient mechanisms of emotional regulation appear essential in understanding the development and maintenance of binge-eating disorder (BED). Previous research focused mainly on a very limited emotion regulation strategies in BED, such as rumination, suppression, and positive reappraisal. Therefore, the aim of the study was to assess a wider range of emotional regulation strategies (i.e. acceptance, refocusing on planning, positive refocusing, positive reappraisal, putting into pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It is noteworthy that people with eating disorders report overall poorer emotion regulation in comparison to people without eating disorders [ 10 ], and that poor emotional awareness and clarity has been found in people with eating disorders [ 11 ]. Studies with samples of people with BED found similar results [ 12 , 13 ]. For instance, limited access to emotion-regulation strategies were associated with BED in people with obesity who were candidates for bariatric surgery [ 12 ].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is noteworthy that people with eating disorders report overall poorer emotion regulation in comparison to people without eating disorders [ 10 ], and that poor emotional awareness and clarity has been found in people with eating disorders [ 11 ]. Studies with samples of people with BED found similar results [ 12 , 13 ]. For instance, limited access to emotion-regulation strategies were associated with BED in people with obesity who were candidates for bariatric surgery [ 12 ].…”
Section: Introductionmentioning
confidence: 53%
“…For instance, limited access to emotion-regulation strategies were associated with BED in people with obesity who were candidates for bariatric surgery [ 12 ]. Moreover, women with BED can experience greater emotion-regulation difficulties, namely nonacceptance of emotional responses, lack of emotional clarity, difficulties engaging in goal-directed behavior, impulse-control difficulties, and limited access to emotion-regulation strategies in comparison to women without BED [ 13 ]. Women with BED may also use more maladaptive emotion-regulation strategies (i.e., rumination, self-blame), and use less adaptive emotion-regulation strategies (i.e., positive refocusing, putting into perspective), in comparison to women without BED [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Before it was tested in binge-eating disorder, LDX was in use for the treatment of children and adults with ADHD. We have mentioned earlier that people with binge-eating disorder have a genetic profile similar to that of people with ADHD and emotional dysregulation is a feature of both (97,98) . The approval of LDX in binge-eating disorder was based on three randomised controlled trials which found LDX superior to placebo for reducing binge-eating days, obsessive-compulsive binge-eating symptoms and body weight (99) .…”
Section: Advances In Drug Treatmentmentioning
confidence: 97%
“…The ability to anticipate, recognise and differentiate between emotions may also be a prerequisite for identifying and flexibly utilising adaptive regulation strategies [11][12][13]. As such, a relationship has indeed been demonstrated between alexithymia and emotion regulation deficits in anorexia nervosa (AN) [14], binge eating disorder (BED) [15] and bulimia nervosa (BN) [16]. People with EDs also struggle to flexibly employ emotion regulation strategies in a context-dependent manner [17], both under-utilising adaptive strategies (like reappraisal and problem-solving) and over-relying on maladaptive ones [4,18].…”
Section: Introductionmentioning
confidence: 99%